Weapon Barrel and Its Additional Accessories - Peter LISÝ (Wojskowa Akademia Techniczna, 2014)
This paper deals with any additional accessories has on a weapon barrel during the initial shot this was done by numerical simulation. This means, that in this paper the influence that the configuration of the assault rifle has on its accuracy is solved. Moreover the weapons muzzle position during the firing of a shot without the influence of temperature or wear of the barrel is solved. The weapon barrel and bullet are both modelled using LS-DYNA software. The barrel is steel and is ideally straight without any structural or manufactured deviations. The bullet is NATO standard 5.56 mm calibre which is consists of a brass jacket and a lead core. The bullets interaction with the barrel during a shot is given by pressured gunpowder gasses both in the barrel and the bullets base whereby it gives the bullet its forward velocity. At the initial stages of the bullets flight it has to overcome its engraving into grooves of the barrel. Both applied pressure and the movement of the bullet along the barrel gives rise to barrel vibration. This barrel vibration has an influence on its muzzle position when the bullet leaves the muzzle. Furthermore, both additional accessories and various conditions of the barrels grip onto the weapons casing have additional influences on the muzzles position when the bullet leaves the muzzle, thus having a great influence on precision
Keywords: Analiza numeryczna drgań lufy podczas strzału